PO33 | Whole blood hypercoagulable profiles in patients with rheumatoid arthritis (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic systemic inflammation resulting in joint deformities and functional loss. Disease activity is accompanied by coagulation abnormalities potentially increasing the risk of venous and arterial thromboembolism. Whether these alterations are associated with a hypercoagulable profile remains a matter of debate. The aim of this case-control study was to evaluate hemostatic system functions in a group of RA patients, using whole blood rotational thromboelastometry and impedance aggregometry.